2009
DOI: 10.1080/00103620802625542
|View full text |Cite
|
Sign up to set email alerts
|

Crop Residue Effects on Organic Carbon, Nitrogen, and Phosphorus Concentrations and Loads in Runoff Water

Abstract: Degraded soil surface conditions favor surface runoff, thus enhancing sediment and nutrient losses. This study examined the effect of crop residues on carbon (C), nitrogen (N), total phosphorus (TP), and total dissolved P (TDP) losses by surface runoff in an agricultural loamy soil with degraded structure. Runoff and sediment yield were made over 1-m 2 plots using a rainfall simulator with constant 65 mmh 21 intensity. Four successive rainfall applications were performed, the first three ones 25 mm each and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
2
13
0
3
Order By: Relevance
“…The NT causes a decrease in total losses of nutrients and organic matter by erosion, due to a decrease in total losses of soil and water compared to CT, despite higher contents of these nutrients and organic matter in runoff water in NT (Avalos et al, 2009;Dantas and Monteiro, 2010;Pugliesi et al, 2011). The effectiveness of the NT system in controlling the loss of plant nutrients and organic matter is unsatisfactory, due to their high contents present in the runoff water and in the eroded sediments (Barbosa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The NT causes a decrease in total losses of nutrients and organic matter by erosion, due to a decrease in total losses of soil and water compared to CT, despite higher contents of these nutrients and organic matter in runoff water in NT (Avalos et al, 2009;Dantas and Monteiro, 2010;Pugliesi et al, 2011). The effectiveness of the NT system in controlling the loss of plant nutrients and organic matter is unsatisfactory, due to their high contents present in the runoff water and in the eroded sediments (Barbosa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On an on-farm study in east central Nebraska, Wienhold and Gilley (2010) observed that corn residue baling at 6 ± 1 Mg ha −1 had no effect on runoff, but it slightly increased sediment loss (0.36 ± 0.02 Mg ha −1 ) compared with no residue removal (0.27 ± 0.01 Mg ha −1 ) when the total amount of residue produced was 12.9 ± 1 Mg ha −1 . Studies of crop residue removal from small plots also found that corn (Mirás-Avalos et al, 2009;Kenney et al, 2015), winter wheat (Triticum aestivum L.), and grain sorghum [Sorghum bicolor (L.) Moench] (Blanco-Canqui and Lal, 2009) residue removal at rates above 50% can increase sediment and nutrient losses.…”
mentioning
confidence: 99%
“…Levando-se em conta apenas o valor de fósforo reativo total obtido neste trabalho, os resultados apontam que o valor tabelado em uso atual fica muito aquém do potencial de risco. Calculando a carga de FRT média dos tratamentos com cobertura vegetal herbácea de F a I, obtém-se o valor médio de 0,1913 t ha -1 ano -1 de P. Mesmo levando em conta os princípios de precaução que se deve ter quanto à extrapolação de dados obtidos em parcelas amostrais em experimento de chuvas simuladas para condições de bacia hidrográfica (Avalos et al, 2009) (2004)), também escolhida como representativa, por reproduzir os métodos atualmente empregados para manejo de fósforo e cobertura de solo para fruticultura em geral, os valores são ainda maiores, chegando a patamares de 3,8794 t ha -1 ano -1 , representando uma diferença 4.640 vezes maior que o valor tabelado.…”
Section: Valores Orientadores De Fósforo Contaminante Para O Rio Granunclassified